Development of A Positive Thinking Measuring Tool for Young Indonesian Muslims - Na'imah, Tri; Dwiyanti, Retno; Sriyanto, Sriyanto; Husen Ismail, Faisal Bin (Universitas Muhammadiyah Yogyakarta, 2023)
A scale based on the Western version of the positive thinking construct can assess the positive thinking capacity of young Indonesian Muslims. However, it can produce biased data since adjusting to the culture is tricky. This research aims to develop a positive thinking measurement tool for young Indonesian Muslims. The research approach used was the exploratory sequential mix method, a qualitative and quantitative research design done in several stages: 1) qualitative research: conducting a qualitative exploration of the positive thinking construct of young Indonesian Muslims and converting the results of qualitative data into scale items; 2) quantitative research: conducting content validation, selecting items, and performing exploratory factor analysis. The content validity test found an average value of V Aiken = 0.8. The dimensions of positive thinking for young Indonesian Muslims included critical thinking, mind control, objective thinking, good prejudice towards Allah, and any other occurrences. The final results of the psychometric analysis found that a positive thinking measuring tool for young Indonesian Muslims consisted of 23 items with a fit factor structure because they had a loading factor greater than 0.5 and reliability of α = 0.702. For future researchers, interventions based on positive thinking can be designed and applied to a sample of adolescents in various cultural contexts.